Comparison of degradation studies in a biosimulator by continuous cultivation of Pseudomonas and indigenous microorganisms with varied dissolved oxygen concentrations. (1st January 2003) - Hashmi, Imran; Kim, Jong-Guk
The aim of this study was to compare the potential of a pure bacterial culture of Pseudomonas with the potential of an indigenous microorganism for malathion degradation by continuous cultivation using two different sets of conditions (with-culture: Pseudomonas, and without-culture: indigenous microorganisms) at varied dissolved oxygen (DO) concentrations (4.0 and 8.0 mg/L) in a biosimulator. The samples were analysed for pH, DO and COD (unfiltered). Gas chromatography (GC) revealed that almost 90% of malathion removal was achieved within ten hours of treatment in both studies of with-culture using 4.0 and 8.0 mg/L DO, whereas COD was considerably reduced during the treatment process and the removal efficiency was found to be above 90% in both conditions. The removal of COD was found to be in direct relation to retention time. However, the unfiltered COD and malathion removal efficiency was significantly influenced by DO. The percentage degradation of malathion using 4.0 mg/L DO, with-culture after 10 hours was 90.01%, whereas after 51 hours it was 99.03%. The without-culture studies showed percentage values which were 38.29% after 10 hours, whereas the corresponding value after 51 hours was 96.84%. Similarly, the percentage degradation of malathion using 8.0 mg/L DO, with-culture studies revealed that almost 89.40% malathion degradation was achieved after 10 hours, whereas it was 96.91% after 51 hours after inoculation of the culture. However, for the without-culture studies the value after 10 hours was 52.34%, whereas 96.86% malathion degradation was achieved after 51 hours without added culture. Although no significant variation in the pH was observed during the study the pH values increased gradually during the treatment process in all of the conditions. A critical evaluation of data presented revealed that the degradation potential of Pseudomonas was better when compared to the degradation potential of indigenous microorganisms.